Novel T cell/organoid culture system allows ex vivo modeling of intestinal graft-versus-host disease - Matthe, Diana M.; Dinkel, Martin; Schmid, Benjamin; Vogler, Tina; Neurath, Markus F.; Poeck, Hendrik; Neufert, Clemens; Büttner-Herold, Maike; Hildner, Kai (Frontiers in Immunology, 2023)
Acute graft-versus-host disease (GvHD) remains the biggest clinical challenge and prognosis-determining complication after allogeneic hematopoietic stem cell transplantation (allo-HSCT). Donor T cells are acceptedly key mediators of alloreactivity against host tissues and here especially the gut. In support of previous studies, we found that the intestinal intra-epithelial lymphocyte (IEL) compartment was dynamically regulated in the course of MHC class I full mismatch allo-HSCT. However, while intestinal epithelial cell (IEC) damage endangers the integrity of the intestinal barrier and is a core signature of intestinal GvHD, the question whether and to what degree IELs are contributing to IEC dysregulation is poorly understood. To study lymphoepithelial interaction, we employed a novel ex vivo T cell/organoid co-culture model system. Here, allogeneic intra-epithelial T cells were superior in inducing IEC death compared to syngeneic IEL and allogeneic non-IEL T cells. The ability to induce IEC death was predominately confined to TCRβ+ T cells and was executed in a largely IFNɣ-dependent manner. Alloreactivity required a diverse T cell receptor (TCR) repertoire since IELs genetically modified to express a TCR restricted to a single, non-endogenous antigen failed to mediate IEC pathology. Interestingly, minor histocompatibility antigen (miHA) mismatch was sufficient to elicit IEL-driven IEC damage. Finally, advanced live cell imaging analyses uncovered that alloreactive IELs patrolled smaller areas within intestinal organoids compared to syngeneic controls, indicating their unique migratory properties within allogeneic IECs. Together, we provide here experimental evidence for the utility of a co-culture system to model the cellular and molecular characteristics of the crosstalk between IELs and IEC in an allogeneic setting ex vivo. In the light of the emerging concept of dysregulated immune-epithelial homeostasis as a core aspect of intestinal GvHD, this approach represents a novel experimental system to e.g. screen therapeutic strategies for their potential to normalize T cell/IEC- interaction. Hence, analyses in pre-clinical in vivo allo-HSCT model systems may be restricted to hereby positively selected, promising approaches.